Barriers and facilitators to infection prevention and control in a neonatal unit in Zimbabwe – a theory-driven qualitative study to inform design of a behaviour change intervention - Herbeć, A; Chimhini, G; Pacareu, JR; Sithole, K; Rickli, F; Chimhuya, S; Manyau, S; Walker, AS; Klein, N; Lorencatto, F; Fitzgerald, F (Elsevier, 2020)
Background Hospital-acquired infection (HAI) is an increasing cause of neonatal morbidity/mortality in low-income settings. Hospital staff behaviours (e.g., hand hygiene) are key contributors to HAI. Understanding the drivers of these can inform interventions to improve infection prevention and control (IPC).